Seed Fertility in Relation to Tree Size of Abies pindrow and Picea smitriana - Arya, S. R.; Bhagat, Sarjan; Singh, Virendra; Singh, Ombir (Indian Forester, 1994)
The effect of size of tree on the fertility of Silver fir and Spruce seed was studied. Although the cone diameters in different diameter breast height class of Silver fir differed significantly at 5% level yet cone lengths did not differ. The seed weights in different diameter breast height classes also differed significantly. However, cone diameters and cone lengths of Spruce did not differ significantly but the seed weights differed significantly. Germination percentages and germination values of seeds from different diameter breast height class trees of Silver fir differed significantly and the same values were, however, non-significant in case of Spruce.